Analisis Efektivitas Dan Efisiensi Pelaksanaan Anggaran Belanja Pada BAPPEDA Dan LITBANG Kabupaten Dompu - Dinda Arista Kholifaturrahmah; I Made Murjana; I Nengah Arsana (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to determine and analyze the level of effectiveness and efficiency of the budget in the 2018-2022 Bappeda & Litbang in Dompu Regency. Data collection techniques used in this study are documentation and interviews. The analytical method used in this study is descriptive quantitative analysis and data analysis using the method of measuring effectiveness and efficiency. The research results show that the effectiveness level of budget implementation at Bappeda & Research and Development of Dompu Regency in 2018-2022 is categorized as effective with an average ratio of effectiveness levels over the last five years of 94.48%. Meanwhile, the overall level of efficiency of the expenditure budget at Bappeda & Research and Development of Dompu Regency in 2018-2022 is categorized as efficient with an average ratio of efficiency level over the last five years of 65.3%.